Interaction quality in political-administrative relations in the United States: Testing a multi-dimensional model - Demir, Tansu; Nank, Renee (2012)
Complementarity has become the new label to characterize the relations between elected officials and professional public administrators. In response to increasingly complex and challenging problems that face local government officials today, public administration scholars have explored how to improve the efficacy of interactions between elected and appointed officials. To do so, scholars have proposed that characteristics of quality interactions include mutual respect, understanding, communication, and partnership between the two parties. Inadequate empirical research, however, exists to help us understand what interaction quality means. This study fills an important gap in the literature by proposing and testing a multi-dimensional model to explain interaction quality. This study utilizes survey data collected from a nationwide sample of city managers in the United States and employs structural equation modeling. - Reproduced.
Keywords: Civil service